On the Effect of Multiple Passes on Kerf Characteristics and Efficiency of Abrasive Waterjet Cutting - Panagiotis Karmiris-Obratański; Nikolaos E. Karkalos; Rafał Kudelski; Emmanouil L. Papazoglou; Angelos P. Markopoulos (Metals, 2021)
Abrasive waterjet cutting is a well-established non-conventional technique for the processing of difficult-to-cut material and rendering of various complex geometries with high accuracy. However, as in every machining process, it is also required that high efficiency and productivity are achieved. For that reason, in the present study, the effect of performing the machining process by multiple passes is investigated, and the evaluation of this approach is performed in terms of total depth of penetration, kerf width, kerf taper angle, mean material removal rate, and cutting efficiency. In the case of multiple passes, the passes are performed in the same direction with the traverse speed adjusted accordingly in order to maintain the total machining time constant in each case. From the experimental results, it was found that the effect of multiple passes on the kerf characteristics, mean material removal rate, and cutting efficiency depends on the process conditions, especially regarding the depth of penetration, and it is possible to achieve significantly higher efficiency by the multi-pass cutting technique when the appropriate process conditions are selected.